2015
DOI: 10.5588/ijtld.14.0454
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lung function according to disease extent before and after pulmonary tuberculosis

Ko Y1,
et al.

Abstract: As the sample size of our study was small, the conclusions could be biased. Nevertheless, our findings show that PTB causes a significant decline in lung function even in localised PTB, whereas advanced PTB was associated with excessive or even higher decline. This study suggests that early diagnosis and treatment of PTB is needed to preserve lung function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Large cross-sectional studies from multiple countries have identified an independent association between a history of TB and OLD [ 41 45 ]. Additionally, retrospective studies have found a history of TB to be associated with excess loss of lung function [ 46 48 ]. Our study is among the first to prospectively assess excess lung function decline in HIV-infected individuals with a history of TB.…”
Section: Discussionmentioning
confidence: 99%
“…Large cross-sectional studies from multiple countries have identified an independent association between a history of TB and OLD [ 41 45 ]. Additionally, retrospective studies have found a history of TB to be associated with excess loss of lung function [ 46 48 ]. Our study is among the first to prospectively assess excess lung function decline in HIV-infected individuals with a history of TB.…”
Section: Discussionmentioning
confidence: 99%
“… 26 These findings are also supported by the smaller cross-sectional, cohort, and case-control studies. 6 , 22 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…2020;46(2):e20180198 3/9 Investigation of changes in pulmonary function after completion of treatment for PTB has been gaining prominence in the literature. (6,7,9,(11)(12)(13)(14)(15)26,27) In our study, the most common functional change in the LDS− group was RLD (24.7%). Cruz et al (15) also described RLD as the main functional change after treatment for PTB; however, that study included patients who underwent more than one treatment for PTB.…”
Section: Discussionmentioning
confidence: 54%
“…However, in a recent study, chest CT and chest X-ray were in disagreement in only 7% of the examinations in patients with PTB sequelae. (26) In addition, chest X-ray is inexpensive and is available at tuberculosis treatment centers in Brazil, in contrast to chest CT, to which access is limited. Another limitation is that pulmonary function was assessed by spirometry only, without plethysmography or DLCO measurement.…”
Section: Discussionmentioning
confidence: 99%